A novel enhanced anti-tetra-missing rib auxetic structure with tailorable in-plane mechanical properties. (1st July 2022) - Zhu, Yilin; Jiang, Songhui; Lu, Fucong; Ren, Xin
Graphical abstract: Highlights: A novel anti-tetra-missing rib structure is proposed. The theoretical models of the structure are proposed. The proposed metamaterial possesses tailorable properties. Abstract: In analogy with the enhanced hexa -missing rib structure, a novel enhanced anti- tetra-missing rib structure was proposed in this work. Using a simple energy-based approach, mechanical modelling under infinitesimal deformation was proposed to provide guidelines for determining the geometries with targeted mechanical properties. It is shown that the proposed structure provides tunable Poisson's ratios and elastic and shear moduli in wide ranges. The analytic solutions of the effective Poisson's ratio, elastic and shear moduli from the mechanics model were validated by systematic finite element (FE) calculations on one unit-cell with considering periodic boundary conditions (PBCs). The underlying deformation mechanism accounting for the auxetic behavior on different geometric parameters of the proposed design was then investigated by elaborated FE analysis in a large deformation regime. The targeted NPR performance was also verified with a nonlinear base material. Uniaxial tensile experiments and the corresponding numerical simulations for lattice structures consisting of an array of proposed unit-cells were also performed to validate the theoretical and FE results obtained from one unit-cell analysis.